Projecting future habitat quality of three midwestern reservoir fishes under warming conditions. Issue 1 (3rd June 2020) - Budnik, Richard R.; Conroy, Joseph D.; Zweifel, Richard D.; Ludsin, Stuart A.; Marschall, Elizabeth A.
Abstract: Rising temperatures caused by climate change are likely to affect cool‐water and warm‐water fishes differently. Yet, forecasts of anticipated temperature effects on fishes of different thermal guilds are lacking, especially in freshwater ecosystems. Towards this end, we used spatially explicit, growth rate potential (GRP) models to project changes in seasonal habitat quality for a warm‐water piscivore (largemouth bass Micropterus salmoides ), a cool‐water piscivore (walleye Sander vitreus ) and a hybrid piscivore (saugeye S. vitreus × S. canadensis ) in two Midwestern reservoirs. We assessed habitat quality for two periods (early and middle 21st century) under two realistic greenhouse gas emission scenarios (a mid‐century emissions peak and a rapid continuous increase in emissions). Largemouth bass were projected to experience enhanced or slightly reduced habitat during all seasons, and throughout the mid‐21st century. By contrast, walleye habitat was projected to decline with anticipated warming, except during the spring in the smaller of our two study reservoirs and during the fall in the larger of our two study reservoirs. Saugeye habitat was projected to either increase modestly or decline slightly during the spring and fall and declines in habitat quality and quantity that were smaller than those for walleye were identified during summer. Collectively, our findings indicate that climate warming will differentially alter habitat suitability for reservoir piscivores, favouring warm‐water species over cool‐water species. We expect these changes in habitat quality to impact the dynamics of reservoir fish populations to varying degrees necessitating the consideration of climate when making future management decisions.